INTEGRATION OF PR TECHNOLOGIES INTO THE MANAGEMENT SYSTEM OF TEAM DYNAMICS AND STAFF BEHAVIOR IN THE CONDITIONS OF DIGITAL TRANSFORMATION OF EDUCATION (Regional aspects of productive forces development of Ukraine, 2026)
Introduction. The article reveals the essence, classification, and applied aspects of integrating PR technologies into the management of team dynamics and staff behavior in educational institutions under conditions of digital transformation. Modern educational organizations face the need to maintain effective communication and support professional cooperation, which strengthens the relevance of PR tools as mechanisms of internal interaction and organizational development. Purpose. The aim of the study is to determine and substantiate the possibilities of integrating PR technologies into the management system of team dynamics and labor behavior of staff in educational institutions. Research Methods. The research methodology is based on general scientific and empirical methods, including analysis, synthesis, systematization, and content analysis of communication practices in educational management. Results. The results of the study clarify the conceptual framework of PR technologies in education and identify key groups of tools that contribute to strengthening internal communication, motivation, and collaboration within academic teams. The influence of digital transformation on changes in communication patterns and forms of team interaction is demonstrated. The paper highlights examples of successful use of PR strategies in Ukrainian and international educational institutions and identifies factors that determine their effectiveness. It is emphasized that PR technologies can support the development of a cohesive corporate culture, reduce resistance to innovation, and increase staff engagement. Conclusions. Integrating PR technologies into the internal communication and management system of educational teams enhances teamwork effectiveness, strengthens trust, and promotes sustainable organizational change. Future research should focus on developing adaptive PR management models tailored to different types of educational teams and digital environments. Keywords: PR technologies, team dynamics, staff behavior, digital transformation, internal communication, corporate culture. Formulas: 0, fig.2: 0, tabl.: 0, bibl.: 17.